Use of botulinum toxin type a for therapeutic purposes (Research, Society and Development, 2021)
The work aims to demonstrate the importance of botulinum toxin in the treatment of pain, presenting the need for a descriptive analysis for the importance of the application and its respective mechanisms of action, seeking a survey in academic articles from ANVISA, CDL and SCIELO in the 1980s a 2014, being the most sought after for use in aesthetics, few people are aware that it can also bring benefits for pain applications. The application of TBA is a treatment in which it varies according to the extension and strength of the muscle to be treated, the greater the strength of the muscle or more extensive, the higher the dose, so the treatment with TBA in addition to having a high degree of satisfaction also has a low rate of complications or side effects.